Strategi Pemberdayaan Kaum Milenial Melalui Program Sekolah Kopi Lampung Barat dalam Upaya Meningkatkan Kesejahteraan Masyarakat - Prastika, Okta; Kagungan, Dian; Meutia, Intan Fitri (Wacana Publik, 2024)
The coffee school is a program built by the West Lampung government in 2019 and inaugurated in 2020. The aim of the research is to analyze the Millennial Empowerment Strategy through the West Lampung Coffee School Program in an Effort to Improve Community Welfare. Data collection techniques through interviews, observation, and documentation by looking at four types of indicators for strategy types, namely Organizational Strategy, Program Strategy, Resource Support Strategy, and Institutional Strategy. The results of this research show that 1). The organization's strategy is based on the vision and mission with output in the form of development programs and improving community resources, especially farmers, in increasing coffee production and quality. 2). Program strategy By implementing the green grading, roasting, cultivation and barista class curriculum, it can have a positive impact on society, 3). Resource support strategy by providing facilities and infrastructure, as well as quality human resources, 4). Institutional strategy carries out responsibilities and authority in accordance with applicable SOPs or regulations. There are factors that hinder the Millennial Empowerment Strategy through the West Lampung Coffee School Program in an effort to improve community welfare, namely the lack of natural resources and the lack of certified tutors.